Environmental education in urban cities: Planet regeneration through ecologically educating children and communities - Vieira, Carolina L Zilli; Rumenos, Nijima Novello; Gheler-Costa, Carla; Toqueti, Flavia; Spazziani, Maria de Lourdes (Elsevier, 2022)
Purpose: In this study, we describe the impact of the Environmental Education (EE) projects for environmental regeneration conducted by the Group of Research and Studies in Environmental Education and Sustainability (GEPEASA) in Brazil. Methods: EE programs have been conducted in National Parks and public schools in urban cities with the objective to include EE in the school curriculum, with school farms, classes of sustainability, food security and environmental health, and recover local green areas. Results: In the areas where EE programs have been applied, there are increases of green areas, ecological consciousness and social engagement, and well-being of students and communities. Conclusions: Lack of ‘nature’ contact is critical in urban areas, where reduced green areas and outdoor activities have created an artificial lifestyle and a false perception of natural reality, increasing the risk of chronic diseases and mental disorders. EE carries the main responsibility to reestablish the connection between nature and children and communities, re-educating them to be the future's conscious Earth's citizens.
Keywords: Ecological conscience and human health; Environmental education; Green spaces